Kegiatan Skrining Kadar Air dan Kadar Minyak pada Kulit dalam Pencegahan Kerusakan Kulit pada Kelompok Usia Produktif - Linda JuliantiWijayadi; Alexander HalimSantoso; Edwin Destra; Yeni Wulandari; Pristia Astari (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
The balance of water and oil levels in the skin is an important factor in maintaining healthy skin, especially in preventing damage due to external factors. In the productive age group, the risk of imbalance in water and oil levels in the skin increases along with environmental exposure and lifestyle. Community service activities are carried out through the Plan-Do-Check-Act (PDCA) approach which includes education about the risk of imbalance in water and oil levels in the skin, as well as routine screening using a skin analyzer. Education focuses on risk factors, prevention, and monitoring of skin conditions, accompanied by counseling on a healthy lifestyle to maintain water and oil levels in the skin. This activity was attended by 40 participants in the productive age group. The results of the examination showed an average water and oil content in the skin on both arms of the participants, with an average value of 56.78% and 25.5% on the right arm, and 53.41% and 23.97% on the left arm. Education succeeded in increasing participants' understanding of the importance of maintaining the balance of water and oil levels in the skin. Maintaining the balance of water and oil levels in the skin has been shown to be important in preventing skin damage. Optimal hydration and proper use of skincare products can minimize the risk of skin imbalance, especially in the productive age group that is vulnerable to environmental exposure.